RADIONUCLIDE DISTRIBUTION AS A MUTAGEN INDUCTION FACTOR AND THREAT TO THE GENETIC RESOURCES OF KYRGYZSTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Radiation and uranium distribution in tailing dumps areas and their impact onlivestock and people are discussed
Keywords: Radiation and uranium distribution in tailing dumps areas and their impact on livestock and people are discussed.